2020
DOI: 10.1016/j.biocontrol.2020.104263
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic plant extracts and coverage mediate larval mosquito survivorship and development

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Floating vegetation can provide a physical barrier between mosquito and oviposition site as well as larvae and air, dissuading oviposition in these areas [ 27 ]. Yet, previous studies have found positive associations between floating vegetation cover and mosquito species presence, suggesting the impacts of this factor on mosquito larvae is complex and context dependent [ 20 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Floating vegetation can provide a physical barrier between mosquito and oviposition site as well as larvae and air, dissuading oviposition in these areas [ 27 ]. Yet, previous studies have found positive associations between floating vegetation cover and mosquito species presence, suggesting the impacts of this factor on mosquito larvae is complex and context dependent [ 20 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dense floating aquatic plants, such as Lemna spp. , can inhibit mosquito larvae and pupae reaching the water surface for air [ 20 , 27 ] Bank vegetation height (cm) The height of vegetation along the ditch margins and banks Increased structural complexity may provide favourable microhabitats for adult mosquitoes and increase availability of sheltered resting places [ 71 ] Bank vegetation cover (%) The percentage of banks covered by plant matter Cover would be expected to provide similar benefits as height Emergent vegetation height (cm) The height of vegetation emerging vertically from the waterbody Emergent vegetation may provide increased shelter for female mosquitoes ovipositing on the water surface and improve larval and pupal survival through predator avoidance [ 69 ] Emergent vegetation cover (%) The percentage area of emergent vegetation Cover would be expected to provide similar benefits as height Shaded water (%) Percentage of water surface shaded Expected to positively impact mosquito species with a preference for heavily vegetated or cool breeding sites. This characteristic also serves as an indicator of reduced habitat openness [ 39 ] Width (cm) Width of the waterbody Wider waterbodies may be more favourable for vertebrate predators, negatively impacting mosquito density [ 76 ].…”
Section: Methodsmentioning
confidence: 99%